Timber Harvesting Margins in the Southern United States: A Temporal and Spatial Analysis - Changyou Sun; Daowei Zhang (Forest Science, 2006)
This study focuses on the logging sector by analyzing timber harvesting margins in the southern United States between 1977 and 2001. The real growth rate of harvesting margins has been negative for pine pulpwood, while positive for pine sawtimber, hardwood pulpwood, and hardwood sawtimber. Harvesting margins for pulpwood are more stable over time and more integrated spatially when compared with those for sawtimber. There is no perfect integration in the logging sector by timber product and no individual state is found to lead the logging service market. The revealed patterns are explained in terms of changing demand for forest products and forest industry structure.